Sessile serrated adenoma/polyp leading to acute appendicitis with multiple pyogenic liver abscesses: A case report. (2018) - Sato, Koki; Banshodani, Masataka; Nishihara, Masahiro; Nambu, Junko; Kawaguchi, Yasuo; Shimamoto, Fumio; Dohi, Kiyohiko; Sugino, Keizo; Ohdan, Hideki
Highlights: Appendicitis with liver abscess and sessile serrated adenoma/polyp is rare. Ileocecal resection was performed for an inflammatory mass in the ileocecum. The patient was successfully treated with a combination of surgery and antibiotics. Abstract: Introduction: Although appendicitis is a common disease, appendicitis concurrent with liver abscesses and sessile serrated adenoma/polyp (SSA/P) is rare. Presentation of case: A 69-year-old man presented with symptoms of abdominal pain and fever. Computed tomography (CT) revealed multiple liver abscesses and an enlarged appendix with a pseudotumoral appearance, which suggested acute appendicitis. In the emergency operation, ileocecal resection was performed for the perforated appendicitis with an inflammatory mass in the ileocecum. On macroscopic examination, the torose lesion was localized at next to the appendiceal orifice. The tumor was diagnosed as SSA/P based on the microscopic finding. The postoperative course was uneventful, and the liver abscesses were cured by antibiotic therapy. The patient was discharged 17 days after the surgery. Discussion: In this case, SSA/P localization at next to the appendiceal orifice was suggested as the cause of the perforated appendicitis with multiple liver abscesses. The patient was successfully treated with a combination of surgery and antibiotic therapy. Conclusion: This is the first reported case of a patient with SSA/P that led to acute appendicitis with multiple pyogenic liver abscesses.